2008
DOI: 10.1007/s00414-008-0292-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive prenatal paternity testing from maternal blood

Abstract: Prenatal paternity analysis can be performed only after invasive sampling of chorionic villi or amnionic fluid. Aiming to enable noninvasive paternity testing, we attempted to amplify fetal alleles from maternal plasma. Cell-free DNA was isolated from plasma of 20 pregnant women and amplified with ampFLSTR Identifiler and ampFLSTR Yfiler kits. Unfortunately, autosomal fetal alleles were heavily suppressed by maternal DNA, and the only locus that was reliably amplified with AmpFLSTR Identifiler kit was amelogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 13 publications
0
24
0
4
Order By: Relevance
“…Amelogenin was the only locus that was reliably amplified by the use of AmpFLSTR. Amelogenin revealed only fetal gender, while the amplification of other autosomal loci was sporadic and insufficient for reliable paternity testing (Wagner et al 2009). The study reported here confirmed the success of this research as being relatively high: approximately 100% for loci of vWA, TH01, D13S317, 100% for amelogenin genes, 90% for loci D18251 and D21S11, giving an average success rate of 96%.…”
Section: Discussionmentioning
confidence: 99%
“…Amelogenin was the only locus that was reliably amplified by the use of AmpFLSTR. Amelogenin revealed only fetal gender, while the amplification of other autosomal loci was sporadic and insufficient for reliable paternity testing (Wagner et al 2009). The study reported here confirmed the success of this research as being relatively high: approximately 100% for loci of vWA, TH01, D13S317, 100% for amelogenin genes, 90% for loci D18251 and D21S11, giving an average success rate of 96%.…”
Section: Discussionmentioning
confidence: 99%
“…Although fetal cfDNA from maternal plasma is reliably measured, 12 and various groups have reported the amplification and detection of fetal-specific alleles using polymerase chain reaction, 13,14,15 these methods do not include sufficient fetal-specific alleles to measure paternity accurately and are not amenable to scaling of interrogated loci.…”
Section: Discussionmentioning
confidence: 99%
“…Because foetal cfDNA sequences are fragmented and generally present in sizes of <150 bp (with few longer than 250 bp) [17], it is difficult to obtain sufficient effective loci using a commercial STR typing kit, especially for a female foetus [9,10]. Although mini-STR analysis has been implemented as an alternative [11], SNP analysis provides a greater guarantee of genotyping fragmented DNA because the variations of interest are much shorter.…”
Section: Introductionmentioning
confidence: 99%
“…In forensic science, recent research has sought to develop a universal approach to non-invasive paternity analysis by genotyping the paternally inherited alleles in the maternal plasma DNA using STR and single-nucleotide polymorphism (SNP) markers [9][10][11][12][13][14][15][16]. Because foetal cfDNA sequences are fragmented and generally present in sizes of <150 bp (with few longer than 250 bp) [17], it is difficult to obtain sufficient effective loci using a commercial STR typing kit, especially for a female foetus [9,10].…”
Section: Introductionmentioning
confidence: 99%